2021
DOI: 10.3390/healthcare9070887
|View full text |Cite
|
Sign up to set email alerts
|

Accreditation and Certification: Do They Improve Hospital Financial and Quality Performance?

Abstract: The relationship between healthcare organizational accreditation and their leaders’ professional certification in healthcare management is of specific interest to institutions of higher education and individuals in the healthcare management field. Since academic program accreditation is one piece of evidence of high-quality education, and since professional certification is an attestation to the knowledge, skills, and abilities of those who are certified, we expect alumni who graduated from accredited programs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In developing countries, various risk factors have been identified that can lead to AEs; they include inadequate health infrastructure and facilities, limited medicines, minimal effort to prevent and control nosocomial infections, low competency, and poor officer performance due to insufficient remuneration, reward systems, lack of education, and training [23]. In addition, the failure of the credential system also affects individual and hospital performances [24]. On the one hand, for whatever reason, patients should not become victims of the weaknesses of the existing management system.…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, various risk factors have been identified that can lead to AEs; they include inadequate health infrastructure and facilities, limited medicines, minimal effort to prevent and control nosocomial infections, low competency, and poor officer performance due to insufficient remuneration, reward systems, lack of education, and training [23]. In addition, the failure of the credential system also affects individual and hospital performances [24]. On the one hand, for whatever reason, patients should not become victims of the weaknesses of the existing management system.…”
Section: Introductionmentioning
confidence: 99%